The Arabidopsis ANGUSTIFOLIA3-YODA Gene Cascade Induces Anthocyanin Accumulation by Regulating Sucrose Levels - Meng, Lai-Sheng; Li, Ying-Qiu; Liu, Meng-Qian; Jiang, Ji-Hong (Frontiers in Plant Science, 2016)
Anthocyanin accumulation specifically depends on sucrose (Suc) signalling/levels. However, the gene cascades specifically involved in the Suc signalling/level-mediated anthocyanin biosynthetic pathway are still unknown. Arabidopsis ANGUSTIFOLIA3 (AN3), a transcription coactivator, is involved in the regulation of leaf shape and drought tolerance. Recently, an AN3-CONSTITUTIVE PHOTOMORPHOGENIC 1 gene cascade has been reported to regulate the light signalling-mediated anthocyanin accumulation. Target gene analysis indicates that AN3 is associated with the YODA (YDA) promoter, a mitogen-activated protein kinase kinase kinase, in vivo for inducing anthocyanin accumulation. Indeed, loss-of-function mutants of YDA showed significantly increased anthocyanin accumulation. YDA mutation can also suppress the decrease in an3-4 anthocyanin accumulation. Further analysis indicates that the mutations of AN3 and YDA disrupt the normal Suc levels because of the changes of invertase activity in mutants of an3 or yda, which in turn induces the alterations of anthocyanin accumulation in mutants of an3 or yda via unknown regulatory mechanisms.